2022
DOI: 10.1038/s41467-022-31980-3
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetically-restricted essential cell cycle progression factor in the human pathogen Candida albicans

Abstract: Chromosomal instability caused by cell division errors is associated with antifungal drug resistance in fungal pathogens. Here, we identify potential mechanisms underlying such instability by conducting an overexpression screen monitoring chromosomal stability in the human fungal pathogen Candida albicans. Analysis of ~1000 genes uncovers six chromosomal stability (CSA) genes, five of which are related to cell division genes of other organisms. The sixth gene, CSA6, appears to be present only in species belong… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Alternative overexpression strategies in C. albicans that involve introducing an extra copy of a gene of interest or introducing an alternative promoter have been used to construct and screen libraries composed of hundreds and even thousands of protein-coding genes ( Rai et al 2021 ). These studies have revealed novel insights into gene function related to morphogenesis ( Chauvel et al 2012 ), cell cycle progression ( Jaitly et al 2022 ), drug tolerance ( Delarze et al 2020 ), and biofilm formation ( Cabral et al 2014 ). Previous comparisons between CRISPRa and ORF-based overexpression libraries in other species have highlighted the potential for these complementary strategies to both confirm findings and unveil distinct genetic hits ( Sanson et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative overexpression strategies in C. albicans that involve introducing an extra copy of a gene of interest or introducing an alternative promoter have been used to construct and screen libraries composed of hundreds and even thousands of protein-coding genes ( Rai et al 2021 ). These studies have revealed novel insights into gene function related to morphogenesis ( Chauvel et al 2012 ), cell cycle progression ( Jaitly et al 2022 ), drug tolerance ( Delarze et al 2020 ), and biofilm formation ( Cabral et al 2014 ). Previous comparisons between CRISPRa and ORF-based overexpression libraries in other species have highlighted the potential for these complementary strategies to both confirm findings and unveil distinct genetic hits ( Sanson et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%